The Price of a Member of Parliament’s Seat. How Much Does It Cost to Convince a Voter? A Comparison of Expenditures on Election Campaigns by Polish Political Parties in 2011–2019 (Economic and Political Thought, 2024)
The text is an analysis of the expenses incurred by electoral committees in the elections to the Polish Parliament in 2011, 2015 and 2019. The principles of financing the election campaign are presented. The analysis mainly concerns the relationship between inflation and expenses, changes in expenses incurred and the costs of winning one parliamentary seat by committees.
Keywords: elections, election campaign, parliamentary mandate, campaign financing, committee expenses